CFD analysis and optimization of nano-enhanced phase change process in multiple port vented cavity equipped with encapsulated PCM under the combined effects of triple rotating cylinders and inclined magnetic field - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier, 2023)
In this study, phase change process dynamics in a multiple vented cavity system equipped with encapsulated phase change materials (PCM) are analyzed under the combined utilization of multiple rotating cylinders and magnetic field. The applications can be found in electronic cooling, rotating type heat exchangers where PCMs are immersed in between and for control purpose of the thermal management. The numerical work is conducted for different values of rotational Reynolds number (Rew, between 0 and 10000), distance between the cylinders (sn between 0.05H and 0.2H), strength of magnetic field (Hartmann number-Ha between 0 and 50) and size of the inlet port (w between 0.075H and 0.25H, H as the cavity size). The phase change process is found to be slower for Rew up to Rew=6000 after which it becomes fast. The full transition time (tF) rises by about 170% at Rew=6000 and then reduces 62% at Rew=10000. At the highest magnetic field, the process intensifies and up to Ha=20, it becomes slower. When magnetic field is active up to Ha=20, the value of tF rises by about 46.5% as compared to case without magnetic field while a reduction of the value by 43.8% is achieved by using magnetic field at the highest strength (Ha=50). Increasing the distance between the triple cylinders and port size of the vented cavity have negative impact on the process both with and without magnetic field. The phase completion time increases by about 124% in the absence of magnetic field when port size is increased from w=0.075H to w=0.25H while the value is 33% with magnetic field at Ha=50. Optimization studies are conducted to find the optimum set of parameter at two different port sizes (w). At w=0.1H, the optimum values are found as (Ha, Rew, sn)=(49.24,4073,0.094H) and at w=0.25H, the values are (Ha, Rew, sn)=(50,2296,0.068H).
Keywords: Vented cavity; Magnetic field; Triple rotating cylinder; FEM; Optimization